The Role Of Employee Involvement In The Influence Of Work Environment Comfort, Communication And Time Management On Employee Performance - Eriza Novita; Agustinus Setyawan; Lily Sudhartio (LPPM Universitas PGRI Sumatera Barat, 2024)
This study examines the role of employee engagement as a mediator in the relationship between workplace comfort, communication, and time management on employee performance within the Provincial Government of Riau Islands. Using primary data collected through accidental sampling, the research involved distributing questionnaires via Google Forms to civil servants who met predefined criteria. The findings indicate that while workplace comfort has a limited direct impact on productivity, effective communication and time management are key factors that significantly contribute to organizational performance. Employee engagement emerged as a strong mediator in these relationships, emphasizing its critical role in enhancing performance outcomes. Theoretical contributions highlight the significant influence of time management and employee engagement in improving employee performance. From a practical perspective, the study suggests that organizations should continuously evaluate these factors and implement policies that promote effective communication, optimal time management, and a comfortable working environment to sustain and improve employee productivity. However, the research is limited to civil servants within the Provincial Government of Riau Islands, which may restrict the generalizability of the findings.